2018
DOI: 10.1101/404780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Tale of Two Positivities and the N400: Distinct neural signatures are evoked by confirmed and violated predictions at different levels of representation

Abstract: Hierarchical prediction has been proposed as a fundamental computational principle underlying neurocognitive processing. Here we ask whether the brain engages distinct neurocognitive mechanisms in response to inputs that fulfill versus violate strong predictions at different levels of representation during language comprehension. Participants read three-sentence scenarios in which the third sentence constrained for a broad event structure (e.g. {Agent caution animate-Patient}). Low constraint contexts did not … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
81
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(100 citation statements)
references
References 106 publications
14
81
5
Order By: Relevance
“…And, indeed, as in many previous studies (e.g. Kuperberg, 2011, 2012;Szewczyk and Schriefers, 2011;Kuperberg, et al, 2019), the evoked N400 response on the subsequent noun was reduced when its animacy features matched (versus mismatched) the animacy constraints of the preceding verb. Moreover, a spatial similarity analysis on the subsequent noun confirmed that the spatial pattern of neural activity was more similar to plausible animate than inanimate nouns (Wang and Kuperberg, Unpublished).…”
Section: The Time Course Of the Prediction Effectsupporting
confidence: 85%
See 2 more Smart Citations
“…And, indeed, as in many previous studies (e.g. Kuperberg, 2011, 2012;Szewczyk and Schriefers, 2011;Kuperberg, et al, 2019), the evoked N400 response on the subsequent noun was reduced when its animacy features matched (versus mismatched) the animacy constraints of the preceding verb. Moreover, a spatial similarity analysis on the subsequent noun confirmed that the spatial pattern of neural activity was more similar to plausible animate than inanimate nouns (Wang and Kuperberg, Unpublished).…”
Section: The Time Course Of the Prediction Effectsupporting
confidence: 85%
“…We suggest that this was the first time point at which comprehenders were able to infer the full high-level event structure (e.g. <Agent cautioned animate noun>), and that they used this structure to generate top-down predictions of the semantic features linked to the animacy of upcoming arguments (Kuperberg and Jaeger, 2016;Kuperberg et al, 2019).…”
Section: The Time Course Of the Prediction Effectmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been observed to vary with integration difficulty (Brouwer, Fitz, & Hoeks, ), conflict resolution (Vissers et al, ), language monitoring (Kolk, Chwilla, Van Herten, & Oor, ), and memory retrieval (see Van Petten & Luka, ). It has been proposed to relate to processes such as revision and repair when unpredicted input is encountered (Kuperberg & Wlotko, ). The posterior PNP/P600’s proposed relation to another ERP, the P3b, has also raised the possibility that it, too, may similarly be affected by the relevance of particular stimuli depending on experimental task (explicitly specified or implicitly perceived by participants; see Van Petten & Luka, , for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, despite consistent reports (see Özyürek, 2014 for review), it remains an open question whether these N400 effects reflect the cost of semantically integrating gesture and language, or the differential level of semantic prediction from gesture to language and vice versa, or a combination of both processes. In fact, in language processing, although the N400 has been classically considered as a semantic integration index (Kutas & Hillyard, 1984), recent functional accounts of the component suggest either the prediction alternative (Bornkessel‐Schlesewsky & Schlesewsky, 2019; Kuperberg, Brothers, & Wlotko, 2020; Kutas & Federmeier, 2011; Lau, Phillips, & Poeppel, 2008), or a hybrid of both processes (Baggio & Hagoort, 2011; Nieuwland et al, 2020).…”
Section: Introductionmentioning
confidence: 99%